#1**0 **

\(0.25r-0.125+0.5r=0.5+r\)** First, you combine like terms.**

\((0.25r+0.5r)-0.125=0.5+r\)

\(0.75r-0.125=0.5+r\)** Then, you subtract r from both sides.**

__- r = - r__

\(-0.25r-0.125=0.5\)** Then, you subtract 0.125 from both sides.**

** - 0.125 = -0.125**

**\(-0.25r=0.375\) Then, because you can't have a neagtive**

** variable, you multiply both sides by -1.**

\(-0.25r*-1=0.375*-1\)

\(0.25r=-0.377\) **Finally**,** you divide both sides by 0.25.**

**\(\frac{0.25r}{0.25}=\frac{-0.375}{0.25}\)**

**\(r=-1.5\)**

**Hope this helps!**

**-RedGlasses **

RedGlasses
Sep 12, 2017

edited by
RedGlasses
Sep 12, 2017

edited by RedGlasses Sep 12, 2017

edited by RedGlasses Sep 12, 2017

edited by RedGlasses Sep 12, 2017

edited by RedGlasses Sep 12, 2017

edited by RedGlasses Sep 12, 2017

edited by RedGlasses Sep 12, 2017

edited by RedGlasses Sep 12, 2017

edited by RedGlasses Sep 12, 2017

#4**0 **

It took me a long time to spot the error in your calculation, but I finally found it! By the way, alignment is always a tricky subject, but you did very well!

However, here is where your error was made. Now, my alignment skills are not up to par either, so bare with me please:

\(-0.25r-0.125=0.5\)

-0.125 -0.125

--------------------------------------

\(-0.25r=\hspace{1cm}0.375\)

However, this is incorrect. It should be the following!

\(-0.25r-0.125=0.5\)

+0.125 +0.125

--------------------------------------

\(-0.25r=\textcolor{red}{0.625}\)

Now, when you solve from here, you will get that \(r=-2.5\).

TheXSquaredFactor
Sep 12, 2017

#2**0 **

I'm sorry, I tried to make all of the words line up, but they didn't. I hope all of what I just said makes sense.

-RedGlasses

RedGlasses
Sep 12, 2017